2010
DOI: 10.1093/bja/aeq257
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance anaesthetics during remifentanil-based anaesthesia might affect postoperative pain control after breast cancer surgery

Abstract: Remifentanil hyperalgesia was induced by high dose of remifentanil-based anaesthesia during sevoflurane anaesthesia, whereas that was not apparent during propofol anaesthesia. Also, remifentanil hyperalgesia did not occur during low dose of remifentanil-based anaesthesia. Maintenance of propofol during high-dose remifentanil-based anaesthesia provided better postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
119
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 30 publications
2
119
0
2
Order By: Relevance
“…The participants were randomly assigned to receive propofol and in control group: thiopental ; thiopental and saline (Anker-Møller et al, 1991); thiopental with halothane ; or, thiopenthal with isoflurane & Jellish et al,1995. In control grup the inhalation anesthetics used were halothane (Hasani et al, 2009), isoflurane (Boccara et al, 1998& Cheng et al,2008, sevoflurane (Ozkose et al,2001, Hofer et al, 2003, Pieters et al, 2010& Shin et al, 2010 and desflurane (Van Hemelrijck et al,1991&Fassoulaki et al, 2010. Also, the control groups contained opioids: fentanyl, remifentanil , Mukherjee et al, 2003& Shin et al, 2010 and alfentanil (Petersen-Felix et al, 1996& Davis et al, 1997.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were randomly assigned to receive propofol and in control group: thiopental ; thiopental and saline (Anker-Møller et al, 1991); thiopental with halothane ; or, thiopenthal with isoflurane & Jellish et al,1995. In control grup the inhalation anesthetics used were halothane (Hasani et al, 2009), isoflurane (Boccara et al, 1998& Cheng et al,2008, sevoflurane (Ozkose et al,2001, Hofer et al, 2003, Pieters et al, 2010& Shin et al, 2010 and desflurane (Van Hemelrijck et al,1991&Fassoulaki et al, 2010. Also, the control groups contained opioids: fentanyl, remifentanil , Mukherjee et al, 2003& Shin et al, 2010 and alfentanil (Petersen-Felix et al, 1996& Davis et al, 1997.…”
Section: Resultsmentioning
confidence: 99%
“…In control grup the inhalation anesthetics used were halothane (Hasani et al, 2009), isoflurane (Boccara et al, 1998& Cheng et al,2008, sevoflurane (Ozkose et al,2001, Hofer et al, 2003, Pieters et al, 2010& Shin et al, 2010 and desflurane (Van Hemelrijck et al,1991&Fassoulaki et al, 2010. Also, the control groups contained opioids: fentanyl, remifentanil , Mukherjee et al, 2003& Shin et al, 2010 and alfentanil (Petersen-Felix et al, 1996& Davis et al, 1997. Intensity of pain scores was considered adequate (>30 mm VAS) in all trials.…”
Section: Resultsmentioning
confidence: 99%
“…Another putative mechanism through which propofol may exert its analgesic properties is through desensitisation of transient receptor potential cation channel, subfamily A, member 1 (TRPA1), a receptor involved in the sensation of pain, cold and itch [36]. In vitro evidence has shown that high concentrations of propofol block TRPA1 activation [37]. A study in mice has also shown that propofol can reduce pain induced by acetic acid by binding to the capsaicin-binding site of transient receptor potential cation channel subfamily-V member 1 (TRPV1), involved in scalding heat and pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in breast cancer surgery also found that propofol was associated with a reduced incidence of chronic postoperative pain [36]. It has also been proposed that propofol might prevent hyperalgesia induced by remifentanil via an NMDA antagonist effect [37]. A recent review found that up to 52% of patients reported long-term pain postoperatively with the only predictive factor being the severity of acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, narcotic opiate regimens, including morphine, are used to treat moderate to severe pain. Paradoxically, patients undergoing chronic opiate therapy have reported abnormal pain, even in regions away from the initial site of pain (4,26,27,49). In addition to tolerance development to the analgesic effects of opiates being a major impediment to pain therapy, chronic opiate-induced hypernociception has become a critical problem.…”
mentioning
confidence: 99%